2019
DOI: 10.1016/j.ebiom.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of sonic hedgehog signaling by a Smoothened agonist restores congenital defects in mouse models of endocrine-cerebro-osteodysplasia syndrome

Abstract: Background: Endocrine-cerebro-osteodysplasia (ECO) syndrome is a genetic disorder associated with congenital defects of the endocrine, cerebral, and skeletal systems in humans. ECO syndrome is caused by mutations of the intestinal cell kinase (ICK) gene, which encodes a mitogen-activated protein (MAP) kinase-related kinase that plays a critical role in controlling the length of primary cilia. Lack of ICK function disrupts transduction of sonic hedgehog (SHH) signaling, which is important for development and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
4
13
0
1
Order By: Relevance
“…Despite these advances, a molecular mechanism by which facial abnormalities develop in animals with reduced cholesterol synthesis has not been characterized. Multiple studies have suggested that defects in cholesterol synthesis are related to altered SHH signaling (Shin et al, 2019), however homozygous Vu57 mutants do not show altered SHH signaling during early CNCC development (Quintana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advances, a molecular mechanism by which facial abnormalities develop in animals with reduced cholesterol synthesis has not been characterized. Multiple studies have suggested that defects in cholesterol synthesis are related to altered SHH signaling (Shin et al, 2019), however homozygous Vu57 mutants do not show altered SHH signaling during early CNCC development (Quintana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is required for the activation of various cell signaling cascades (Shimomura et al, 2019), including SHH and WNT, both of which are required for craniofacial development (Shimomura et al, 2019; Shin et al, 2019). For example, WNT activation requires the activity of dishevelled, a scaffolding protein (Bernatik et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances, a molecular mechanism by which facial abnormalities develop in these animals has not been characterized. Multiple studies have suggested that defects in cholesterol synthesis are related to defects in SHH signaling (Shin et al, 2019), however homozygous mutation of the Vu57 allele does not affect SHH signaling (Quintana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is required for the activation of various cell signaling cascades (Shimomura et al, 2019), including SHH and WNT, both of which are required for craniofacial development (Shimomura et al, 2019; Shin et al, 2019). For example, WNT activation requires the activity of disheveled, a scaffolding protein (Bernatik et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal cell kinase ( ICK ) gene encoding for a mitogen-activated protein (MAP) kinase involved in activating Shh signaling during development is downregulated during endocrine-cerebro-osteodysplasia (ECO), a syndrome that includes CP. As the first study to attempt prenatal pharmaceutical activation of Shh signaling, Shin et al (2019) injected a small-molecule agonist for Smoothened (SAG) intraperitoneally into pregnant Ick tm1a/+ mice at various stages. Although success in palatal closures showed variable efficacy, the highest efficiency was achieved at E11.25, indicating that developmental windows are critical for restoring molecular homeostasis in Shh-mediated actions.…”
Section: Prenatal Approachesmentioning
confidence: 99%